(untitled) (Legal journal - Research in Legal and Social Sciences, 2023)
This research addresses issues related to the origins and modifications through protocols of the Charter of the Organization of American States, hereinafter OAS, and specifies the pillars on which the organization is based. In this regard, it describes the bodies in charge of its administration and details the function performed by each one. On this point, special mention is made of the Inter-American Juridical Committee, hereinafter IJC, date of creation, members, agenda, and the work it performs, specifying the documents that emanate from it, which are submitted to the General Assembly. In this context of internationality, Paraguay’s participation stands out both in the membership of the IJC and in the assignment of representatives to the meetings convened by the General Assembly, in order to decide on issues for consideration. Therefore, the dynamic intervention of the Paraguayan State with regard to international law makes it a participant in the progress of the legal system at the regional level. In view of the fact that this is the starting point for understanding the importance of the studies and debates carried out by the IJC, which subsequently become part of the domestic law of each member country of the organization. As for the method used, it responds to the bibliographic review, which implies the realization of a documentary research, non-experimental type with a qualitative analysis.